Manual de beneficio del cacao 2008 :para técnicos, profesionales del sector agropecuario y productores - Merizalde, Gabriel Jaime; Correa, Elizabeth; Cubillos, Gabriel (Gobernación de Antioquia, 2018)
Cacao-Theobroma cacao